THE USE OF INSTAGRAM @INFO_BEASISWA AS A MEDIUM FOR FULFILLING SCHOLARSHIP INFORMATION NEEDS: A MEDIA RICHNESS THEORY PERSPECTIVE - Ihthia Dewi Ramdani; Annisa Fajriyah; Firma Sahrul Bahtiar (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
Scholarship information is time-sensitive, detailed, and closely related to educational decision-making, requiring digital media that can present information clearly, relevantly, and accessibly. This study analyzes the Instagram account @info_beasiswa as a medium for fulfilling scholarship information needs from the perspective of Media Richness Theory. The novelty of this study lies in applying Media Richness Theory to a popular Instagram account specifically dedicated to scholarship information in the context of educational information needs. This research employed a descriptive quantitative approach involving 100 followers selected through purposive sampling. Data were collected using a four-point Likert-scale questionnaire consisting of 23 items and were supported by observation, documentation, and brief interviews with the account manager. The analysis focused on four dimensions: immediacy of feedback, multiple cues, language variety, and personal focus. The findings show that all dimensions were in the very high category, with multiple cues obtaining the highest grand mean score (3.53), followed by language variety (3.45), personal focus (3.39), and immediacy of feedback (3.31). These results indicate that @info_beasiswa mainly supports followers’ information needs through varied content formats, visual presentation, clear language, and relevant scholarship content, although rapid interpersonal feedback remains the least dominant dimension. This study contributes to library and information science by showing how Instagram can function as an intermediary information source for recognizing, understanding, and following up scholarship opportunities.